Fenofibrate Attenuates Malignant Hypertension by Suppression of the Renin-angiotensin System: A Study in Cyp1a1-Ren-2 Transgenic Rats - Jíchová, Šárka; Doleželová, Šárka; Kopkan, Libor; Kompanowska-Jezierska, Elzbieta; Sadowski, Janusz; Červenka, Luděk (The American journal of the medical sciences, 2016)
BACKGROUND: Malignant hypertension is a life-threatening condition, and its pathophysiology is still poorly understood. The present study was designed to evaluate the role of interaction of the renin-angiotensin system with 20-hydroxyeicosatetraenoic acid (20-HETE), a product of cytochrome P450 (CYP)-dependent ω-hydroxylase pathway, in the pathophysiology of angiotensin II (ANG II)-dependent malignant hypertension in Cyp1a1-Ren-2 transgenic rats. METHODS: Malignant hypertension was induced by 12 days׳ dietary administration of 0.3 % indole-3-carbinol (I3C), a natural xenobiotic that activates a mouse renin gene. We hypothesized that chronic administration of fenofibrate, 190mg/kg body weight, a lipid-lowering drug, should increase renal production of 20-HETE, a tubular transport inhibitor; an expected increase in sodium excretion would oppose the development of ANG II-dependent malignant hypertension. Blood pressure was monitored by radiotelemetry, and at the end of the experiment rats were prepared for renal functional studies to evaluate in vivo the pressure-natriuresis relationship in response to stepwise reductions in renal arterial pressure (RAP). RESULTS: In I3C-induced rats, the treatment with fenofibrate significantly attenuated hypertension and improved the slope of the pressure-natriuresis relationship. Although fenofibrate treatment increased kidney gene and protein expression of CYP4A1, a major isoform responsible for 20-HETE formation, it did not increase renal 20-HETE concentration. On the contrary, fenofibrate treatment significantly suppressed renin gene expression, plasma renin activity and plasma and kidney ANG II levels. CONCLUSIONS: Fenofibrate treatment significantly attenuated the course of malignant hypertension in I3C-induced CYP1a1-Ren-2 transgenic rats, and the mechanism responsible for antihypertensive action was fenofibrate-induced suppression of renin-angiotensin system activity.
Keywords: hodnoty glomerulární filtrace; Transcriptional Activation; Indoles; Renin-angiotensin system; Renin; krevní tlak; Male; renální oběh; fenofibrát; mužské pohlaví; cytochrom P450 CYP4A; cytochrom P-450 CYP1A1; renin-angiotensin systém; Malignant hypertension; Rats, Transgenic; Cytochrome P450 metabolites; hypertenze maligní; Fenofibrate; renin; Natriuresis; 20-hydroxyeicosatetraenoic acid; zvířata; Blood Pressure; Renal Circulation; homeostáza; Cytochrome P-450 CYP4A; aktivace transkripce; ledviny; Hypertension, Malignant; Hydroxyeicosatetraenoic Acids; Renin-Angiotensin System; kyseliny hydroxyeikosatetraenové; indoly; potkani transgenní; Kidney; natriuréza; Homeostasis; Glomerular Filtration Rate; Cytochrome P-450 CYP1A1; Animals